Do the millennials in the USA care about the fast food industry's involvement in corporate social responsibility?. Issue 4 (23rd October 2018) - Harun, Ahasan; Prybutok, Gayle; Prybutok, Victor
Abstract : Purpose: This purpose of this paper is to develop and examine a theoretical framework for evaluating role of corporate social responsibility (CSR) in influencing millennial fast food consumers' purchasing behavior. It also aims to help business strategists to leverage marketing strategies to achieve a competitive gain. Design/methodology/approach: To examine the proposed framework through the partial least squares structural equation modeling (PLS-SEM), the authors collected data through survey. They also evaluated the proposed framework through the multi-group analysis and the importance-performance map analysis (IPMA). Findings: Findings suggest that CSR alone is unable to influence millennial fast food consumers' purchase intention. Therefore, fast food business strategists should communicate CSR activities by simultaneously focusing on affective identification and satisfaction to achieve the objective. IPMA analysis shows that, among all the CSR indicators, fast food restaurants' responsible behavior and their concern with respect to the environment create the most impact on millennial fast food consumers' mindset. Practical implications: For fast food business strategists, the findings of this research provide a strategic blueprint in terms of using CSR as a way to foster relationships with the millennial fast food consumers, thus creating a competitive advantage in the market. Originality/value: Anchoring in the theoretical framework, this research contributes to the extant literature by providing a critical evaluation of how to influence millennial fast food consumers' purchase intention from a more systematic perspective. This research also offers fast food marketing managers a strategy by leveraging their initiatives for a particular customer segment through the IPMA at both the construct and indicator levels.